2015
DOI: 10.1002/ejic.201500925
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Thermochromism in a Gold(I)–Copper(I) Phosphine–Pyridine Complex

Abstract: The AuI complex [Au(Ph2PCH2py)2]BF4 (1) was prepared by mixing (tetrahydrothiophene)gold(I) chloride with 2‐[(diphenylphosphino)methyl]pyridine (Ph2PCH2py) in dichloromethane. The addition of [Cu(NCCH3)4]BF4 to 1 produced green‐luminescent [AuCu(Ph2PCH2py)2(NCCH3)2](BF4)2 (2). When crystals of 2 were exposed to air, two acetonitrile molecules were lost to form crystals of yellow‐luminescent [AuCu(Ph2PCH2py)2](BF4)2 (3). This simple solvent loss perturbs the environment around the CuI center, and the Au···Cu di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
(56 reference statements)
0
25
0
Order By: Relevance
“…It was observed that the wavelength of emission shows a strong linear correlation with the solution temperature while inside the temperature range in which MeTHF is liquid. Additionally, the TTz/MeTHF solution showed relatively high temperature sensitivity (−0.21 nm °C –1 ), thus making it suitable for temperature-sensing applications. …”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the wavelength of emission shows a strong linear correlation with the solution temperature while inside the temperature range in which MeTHF is liquid. Additionally, the TTz/MeTHF solution showed relatively high temperature sensitivity (−0.21 nm °C –1 ), thus making it suitable for temperature-sensing applications. …”
Section: Resultsmentioning
confidence: 99%
“…Dinuclear Au–Cu phosphine complex 79 (Figure ) shows thermochromic luminescence with three distinct colors ( λ em =543 nm/77–298 K, λ em =551 nm/298–343 K, λ em =505 nm/>343 K) and a solvochromic effect towards CH 3 CN ( λ em =536 nm) in the crystalline state …”
Section: Acyclic Organophosphorus Compoundsmentioning
confidence: 99%
“…[1][2][3][4] In particular, thermo-responsive functional materials with specific luminescence changes have attracted wide attention due to their potential applications in temperature sensing, [5][6][7][8][9][10][11][12] biological imaging, [13][14][15][16][17][18][19][20] optoelectronic devices, [21][22][23][24][25] and information processing. [26][27][28] To date, tremendous progress has been made in the development of thermo-responsive light-emitting materials, including various organic dyes and polymers, [29][30][31][32][33][34][35][36][37] metal complexes, [38][39][40][41][42][43][44] metal clusters and metal-organic frameworks (MOFs), [45][46][47][48]…”
Section: Introductionmentioning
confidence: 99%